A method for preparing high-strength anti-pollution ultrafiltration membrane
By reacting the nitrogen-olsis with catechin catelin-炔 炔 炔 通过 通过 通过 通过 通过 通过 炔 炔 炔 炔 炔 通过 通过 通过 通过 通过 通过 通过 通过 通过 通过 通过 通过 通过 polypropylene superfractive membrane is prepared to solve the mechanical performance and anti-pollution performance of polypropylene hyperfilty membrane Poor problems realize higher tensile strength, hydrophilicity and anti -pollution performance.
Patent Information
- Application Number
- CN202411420127.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The polyacrylonitrile ultrafiltration membrane has poor mechanical properties, poor anti-pollution performance, and low hydrophilicity and water flux.
By carrying out azide-alkyne reaction between alkynyl polyacrylonitrile copolymer and azido cellulose acetate, cellulose acetate grafted polyacrylonitrile is prepared to enhance the compatibility and interfacial interaction between the two. Avoid phase separation.
It improves the stretching strength and fracture and elongation of the ultra -filter membrane, enhance the hydrophilicity and water flux, and improve the anti -pollution performance.
Smart Images

Figure CN118925504B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ultrafiltration membranes, and in particular to a method for preparing a high-strength anti-pollution ultrafiltration membrane. Background Art
[0002] Polyacrylonitrile ultrafiltration membrane has the advantages of low cost, high thermal stability, good solvent resistance, excellent antibacterial and mildew resistance, etc. It has important applications in protein separation and purification, sewage treatment, etc. Traditional polyacrylonitrile ultrafiltration membrane has poor hydrophilicity, low water flux, poor mechanical properties and anti-protein pollution properties, which limits the development and application of polyacrylonitrile ultrafiltration membrane.
[0003] The copolymerization of acrylonitrile with monomers such as acrylic acid, methyl methacrylate, and vinylpyridine can improve the hydrophilicity of polyacrylonitrile ultrafiltration membrane, water flux and other properties. Cellulose is cheap and easy to obtain, green and pollution-free, and has good hydrophilicity and high mechanical strength, and is widely used in ultrafiltration membrane materials. Patent technology document CN113457475A polyacrylonitrile / nano whisker composite ultrafiltration membrane and its preparation method discloses that polyacrylonitrile and nanocellulose are blended and phase inversion is used to prepare membranes, thereby improving the hydrophilicity of ultrafiltration membranes, strength and other properties. However, the compatibility of cellulose and polyacrylonitrile is poor, and the two are blended to prepare membranes, which is prone to interface incompatibility and phase separation, affecting the performance of ultrafiltration membranes. Summary of the invention
[0004] (I) Technical problems to be solved: The present invention provides a method for preparing a high-strength anti-pollution ultrafiltration membrane, which solves the problems of poor mechanical properties, poor anti-pollution performance, low hydrophilicity and water flux of polyacrylonitrile ultrafiltration membrane.
[0005] (II) Technical solution: A method for preparing a high-strength anti-pollution ultrafiltration membrane:
[0006] Step A, adding dimethyl sulfoxide, acrylonitrile, acrylate butyric acid amide alkynyl monomer into a reaction container, introducing nitrogen, adding azobisisobutyronitrile, stirring for reaction, cooling and pouring the solution into water for precipitation, filtering and washing with water and ethanol in turn, and drying to obtain an alkynyl polyacrylonitrile copolymer;
[0007] The structural formula of acrylate butyric acid amide acetylenic monomer is: .
[0008] Step B: Add pyridine and cellulose acetate to a reaction container, heat to 55-60° C., stir, add 4-azidobenzoyl chloride (CAS registration number: 14848-01-2), heat to 70-85° C., stir and react for 3-6 hours, cool, pour the solution into water for precipitation, filter, wash with ethanol, and dry to obtain azido cellulose acetate.
[0009] Step C, add N,N-dimethylformamide, alkynyl polyacrylonitrile copolymer, azido cellulose acetate into a reaction container, stir and mix, add sodium ascorbate, copper sulfate, water, introduce nitrogen, stir and react, pour the solution into water for precipitation after cooling, filter, wash with water, and dry to obtain cellulose acetate grafted polyacrylonitrile.
[0010] Step D: add dimethyl sulfoxide and cellulose acetate grafted polyacrylonitrile into a container, stir to dissolve and then stand to degas, then pour the solution onto the surface of a clean glass plate, cast and scrape the film, then soak the glass plate in distilled water to perform phase transformation into a membrane, and soak and wash the obtained membrane material in distilled water for 48 hours, change the distilled water every 6 hours, and then dry to obtain a high-strength anti-pollution ultrafiltration membrane.
[0011] Furthermore, in step A, the amount of acrylonitrile is 100 parts by weight, the amount of acrylate butyric acid amide acetylenic monomer is 4-25 parts by weight, and the amount of azobisisobutyronitrile is 0.82-0.96 parts by weight.
[0012] Furthermore, in step A, the reaction is carried out at a temperature of 60-70° C. for 5-8 h.
[0013] Furthermore, in step B, the amount of pyridine used is 1500-2000 parts by weight, the amount of cellulose acetate is 100 parts by weight, and the amount of 4-azidobenzoyl chloride is 5-40 parts by weight.
[0014] Furthermore, in step C, the amount of alkynyl polyacrylonitrile copolymer is 100 parts by weight, cellulose acetate azido is 20-40 parts by weight, sodium ascorbate is 1.2-2.5 parts by weight, and copper sulfate is 0.7-1.6 parts by weight.
[0015] Furthermore, in step C, the reaction is carried out at a temperature of 45-70° C. for 18-36 hours.
[0016] Furthermore, the preparation method of the acrylate butyric acid amide alkynyl monomer is as follows: add tetrahydrofuran or 1,4-dioxane solvent, 100 parts by weight of propargylamine, 320-360 parts by weight of 2-bromoethyl acrylate (CAS registration number 4823-47-6) into a reaction container, heat to 30-40°C, carry out substitution reaction for 12-18h, then add 190-220 parts by weight of succinic anhydride, heat to 35-50°C, carry out amidation reaction for 2-5h, concentrate the solution under reduced pressure, wash with methanol, and recrystallize the product in dichloromethane to obtain the acrylate butyric acid amide alkynyl monomer.
[0017] (III) Technical Effect: The present invention uses propargylamine, 2-bromoethyl acrylate and succinic anhydride as reactants to prepare acrylate butyric acid amide acetylenic monomer by a one-pot method, and then polymerizes it with acrylonitrile monomer to obtain a polyacrylonitrile copolymer containing acetylenic groups and carboxyl groups.
[0018] The present invention utilizes 4-azidobenzoyl chloride to react with the hydroxyl group of cellulose acetate to obtain azido cellulose acetate, and then carries out an azide-alkyne reaction with an alkynyl polyacrylonitrile copolymer, thereby carrying out a grafting reaction between cellulose acetate and polyacrylonitrile, enhancing the compatibility between the two, improving the interface interaction force, avoiding the phenomenon of phase separation between the two due to interface incompatibility, thereby making the ultrafiltration membrane have higher tensile strength and elongation at break, and showing better mechanical properties.
[0019] The present invention uses cellulose acetate grafted polyacrylonitrile as the substrate of the ultrafiltration membrane. The membrane matrix contains carboxyl and triazole hydrophilic groups, so that the ultrafiltration membrane exhibits better hydrophilicity, which is beneficial to enhancing the hydrophilicity and water flux of the ultrafiltration membrane.
[0020] The ultrafiltration membrane of the present invention has strong hydrophilicity and contains carboxyl and triazole groups, which have strong hydrogen bond interactions with water molecules, so that the water molecules form a water film on the surface of the ultrafiltration membrane, reduce the contact between proteins and the ultrafiltration membrane, and avoid protein attachment to the surface and pores of the ultrafiltration membrane, thereby making the ultrafiltration membrane exhibit better anti-pollution performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is the reaction formula for preparing acrylate butyric acid amide acetylenic monomer.
[0022] Figure 2 It is an acetylenic polyacrylonitrile copolymer.
[0023] Figure 3 This is the reaction formula for the preparation of cellulose azidoacetate.
[0024] Figure 4 This is the reaction formula for preparing cellulose acetate grafted with polyacrylonitrile. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0026] (1) Add tetrahydrofuran solvent, 0.4 g of propargylamine, and 1.44 g of 2-bromoethyl acrylate to a reaction container, heat to 40° C., and carry out substitution reaction for 12 hours. Then, add 0.76 g of succinic anhydride, heat to 50° C., and carry out amidation reaction for 2 hours. The solution is concentrated under reduced pressure, washed with methanol, and the product is recrystallized in dichloromethane to obtain an acrylate butyric acid amide alkynyl monomer.
[0027] (2) Add 250 mL of dimethyl sulfoxide, 50 g of acrylonitrile, and 12.5 g of acrylate butyric acid amide acetylenic monomer into a reaction container, introduce nitrogen, heat to 70°C, add 0.48 g of azobisisobutyronitrile, stir and react for 6 h, cool and pour the solution into water for precipitation, filter and wash with water and ethanol in turn, and dry to obtain an acetylenic polyacrylonitrile copolymer.
[0028] (3) Add 400 g of pyridine and 20 g of cellulose acetate to a reaction container, heat to 60°C, stir, then add 8 g of 4-azidobenzoyl chloride, heat to 80°C, stir and react for 4 h, cool, pour the solution into water for precipitation, filter, wash with ethanol, and dry to obtain azido cellulose acetate.
[0029] (4) Add 200 mL of N,N-dimethylformamide, 50 g of acetylenic polyacrylonitrile copolymer, and 10 g of azidocellulose acetate into a reaction container, stir to mix, add 0.6 g of sodium ascorbate, 0.35 g of copper sulfate, and 15 mL of water, introduce nitrogen, heat to 50°C, stir to react for 24 h, cool, pour the solution into water for precipitation, filter, wash with water, and dry to obtain cellulose acetate grafted polyacrylonitrile.
[0030] (5) Add 700 mL of dimethyl sulfoxide and 100 g of cellulose acetate grafted polyacrylonitrile into a container, stir to dissolve and then let stand to degas. Then pour the solution onto the surface of a clean glass plate and cast a film. Then, soak the glass plate in distilled water to perform phase transformation to form a membrane. The obtained membrane material is soaked and washed in distilled water for 48 h. The distilled water is changed every 6 h and then dried to obtain a high-strength anti-fouling ultrafiltration membrane. Example 2
[0031] (1) 1,4-dioxane solvent, 0.4 g of propargylamine, and 1.28 g of 2-bromoethyl acrylate were added to a reaction vessel, and a substitution reaction was carried out at 30° C. for 18 h. Then, 0.88 g of succinic anhydride was added, and the mixture was heated to 35° C. to carry out an amidation reaction for 5 h. The solution was concentrated under reduced pressure, washed with methanol, and the product was recrystallized in dichloromethane to obtain an acrylate butyric acid amide alkynyl monomer.
[0032] (2) Add 250 mL of dimethyl sulfoxide, 50 g of acrylonitrile, and 7 g of acrylate butyric acid amide acetylenic monomer into a reaction container, introduce nitrogen, heat to 60°C, add 0.45 g of azobisisobutyronitrile, stir and react for 8 h, cool and pour the solution into water for precipitation, filter and wash with water and ethanol in turn, and dry to obtain an acetylenic polyacrylonitrile copolymer.
[0033] (3) Add 360 g of pyridine and 20 g of cellulose acetate to a reaction container, heat to 55°C, stir, then add 5 g of 4-azidobenzoyl chloride, heat to 85°C, stir and react for 3 h, cool, pour the solution into water for precipitation, filter, wash with ethanol, and dry to obtain azido cellulose acetate.
[0034] (4) Add 300 mL of N,N-dimethylformamide, 50 g of acetylenic polyacrylonitrile copolymer, and 13 g of azidocellulose acetate into a reaction container, stir and mix, add 0.78 g of sodium ascorbate, 0.46 g of copper sulfate, and 20 mL of water, introduce nitrogen, heat to 70°C, stir and react for 18 h, cool, pour the solution into water for precipitation, filter, wash with water, and dry to obtain cellulose acetate grafted polyacrylonitrile.
[0035] (5) Add 700 mL of dimethyl sulfoxide and 100 g of cellulose acetate grafted polyacrylonitrile into a container, stir to dissolve and then let stand to degas. Then pour the solution onto the surface of a clean glass plate and cast a film. Then, soak the glass plate in distilled water to perform phase transformation to form a membrane. The obtained membrane material is soaked and washed in distilled water for 48 h. The distilled water is changed every 6 h and then dried to obtain a high-strength anti-fouling ultrafiltration membrane. Example 3
[0036] (1) Add 200 mL of dimethyl sulfoxide, 50 g of acrylonitrile, and 2 g of acrylate butyric acid amide acetylenic monomer (prepared in the same manner as in Example 1) into a reaction container, introduce nitrogen, heat to 70° C., add 0.41 g of azobisisobutyronitrile, stir and react for 5 h, cool, pour the solution into water for precipitation, filter, wash with water, ethanol, and dry to obtain an acetylenic polyacrylonitrile copolymer.
[0037] (2) Add 300 g of pyridine and 20 g of cellulose acetate to a reaction container, heat to 55°C, stir, then add 1 g of 4-azidobenzoyl chloride, heat to 70°C, stir and react for 6 h, cool, pour the solution into water for precipitation, filter, wash with ethanol, and dry to obtain azido cellulose acetate.
[0038] (3) Add 300 mL of N,N-dimethylformamide, 50 g of acetylenic polyacrylonitrile copolymer, and 16 g of azido cellulose acetate into a reaction container, stir and mix, add 1.04 g of sodium ascorbate, 0.67 g of copper sulfate, and 20 mL of water, introduce nitrogen, heat to 45°C, stir and react for 36 hours, cool, pour the solution into water for precipitation, filter, wash with water, and dry to obtain cellulose acetate grafted polyacrylonitrile.
[0039] (4) Add 800 mL of dimethyl sulfoxide and 100 g of cellulose acetate grafted polyacrylonitrile into a container, stir to dissolve and then let stand to degas. Then pour the solution onto the surface of a clean glass plate and cast a film. Then, soak the glass plate in distilled water to perform phase transformation to form a membrane. The obtained membrane material is soaked and washed in distilled water for 48 hours. The distilled water is changed every 6 hours and then dried to obtain a high-strength anti-pollution ultrafiltration membrane. Example 4
[0040] (1) Add 300 mL of N,N-dimethylformamide, 50 g of acetylenic polyacrylonitrile copolymer (prepared in the same manner as in Example 1), and 20 g of azido cellulose acetate (prepared in the same manner as in Example 1) into a reaction container, stir and mix, add 1.25 g of sodium ascorbate, 0.8 g of copper sulfate, and 20 mL of water, introduce nitrogen, heat to 50° C., stir and react for 36 h, cool, pour the solution into water for precipitation, filter, wash with water, and dry to obtain cellulose acetate grafted polyacrylonitrile.
[0041] (2) Add 800 mL of dimethyl sulfoxide and 100 g of cellulose acetate grafted polyacrylonitrile into a container, stir to dissolve and then let stand to degas. Then pour the solution onto the surface of a clean glass plate and cast a film. Then, soak the glass plate in distilled water to perform phase transformation to form a membrane. The obtained membrane material is soaked and washed in distilled water for 48 hours. The distilled water is changed every 6 hours and then dried to obtain a high-strength anti-fouling ultrafiltration membrane.
[0042] Comparative Example 1
[0043] (1) Add 250 mL of dimethyl sulfoxide and 50 g of acrylonitrile to a reaction vessel, introduce nitrogen, heat to 70°C, add 0.48 g of azobisisobutyronitrile, stir and react for 6 h, cool and pour the solution into water for precipitation, filter and wash with water and ethanol in turn, and dry to obtain polyacrylonitrile.
[0044] (2) Add 700 mL of dimethyl sulfoxide and 100 g of polyacrylonitrile into a container, stir to dissolve and then let stand to degas. Then pour the solution onto a clean glass plate and cast a film. Then soak the glass plate in distilled water to perform phase transformation to form a membrane. The obtained membrane material is soaked and washed in distilled water for 48 hours. The distilled water is changed every 6 hours and then dried to obtain an ultrafiltration membrane.
[0045] Comparative Example 2
[0046] (1) Add 700 mL of dimethyl sulfoxide and 100 g of acetylene polyacrylonitrile copolymer (prepared according to the method of Example 1) into a container, stir to dissolve and then stand to degas. Then pour the solution onto the surface of a clean glass plate and cast a film. Then, soak the glass plate in distilled water to perform phase transformation to form a membrane. The obtained membrane material is immersed in distilled water for washing for 48 hours, and the distilled water is changed every 6 hours. Then, it is dried to obtain an ultrafiltration membrane.
[0047] Comparative Example 3
[0048] (1) Add 700 mL of dimethyl sulfoxide, 100 g of acetylene polyacrylonitrile copolymer (prepared according to the method of Example 1), and 20 g of cellulose acetate into a container, stir to dissolve, and then stand to degas. Then pour the solution onto the surface of a clean glass plate and cast a film. Then, soak the glass plate in distilled water to perform phase conversion to form a membrane. The obtained membrane material is soaked and washed in distilled water for 48 hours, and the distilled water is changed every 6 hours. Then, it is dried to obtain an ultrafiltration membrane.
[0049] The ultrafiltration membrane was made into 8cm×1cm×0.2cm samples, and the tensile properties of the samples were tested using a universal material testing machine. The tensile rate was 5mm / min, and the distance between the samples between the clamps was 3cm. Each group of samples was tested 5 times and the average value was taken.
[0050] The contact angle of the membrane was tested using a static water contact instrument. Each group of samples was tested 5 times and the average value was taken.
[0051] The ultrafiltration membrane was cut into circular membranes, and the pure water flux of the circular membranes was tested using a membrane pure water flux meter. The pressure during the test was 0.1 MPa, and the membrane was pre-pressed at a pressure of 0.15 MPa for 30 minutes before the test.
[0052] Pure water flux J 0 =V / (A×t). A is the effective membrane area of the circular membrane, t is the time. V is the volume of pure water that passes through the circular membrane in time t.
[0053] Anti-pollution performance test: The flux of the circular membrane to bovine serum albumin aqueous solution (mass fraction 500 mg / L) was tested using a membrane pure water flux meter. 1 The pressure during the test was 0.1 MPa. Before the test, distilled water was used to pre-press the membrane at a pressure of 0.15 MPa for 30 minutes. After the test, the circular membrane was washed with distilled water; then the pure water flux of the circular membrane was tested. 2 .
[0054] Calculate the pollution index R and flux recovery rate P.
[0055] R = (J 0-J 1 ) / J 2 ×100%. The smaller the pollution index R, the better the anti-pollution performance.
[0056] Flux recovery rate P=J 2 / J 0 ×100%. The greater the flux recovery rate, the better the anti-pollution performance.
[0057] Table 1 Ultrafiltration membrane tensile performance test
[0058]
[0059] As shown in Table 1, in Comparative Examples 1 and 2, polyacrylonitrile and acetylene polyacrylonitrile copolymer are used as the substrates of the ultrafiltration membranes, and the tensile strengths are only 2.11 MPa and 2.05 MPa, and the elongations at break are only 45.6% and 42.8%.
[0060] In Examples 1-4, acetylene polyacrylonitrile copolymer and azido cellulose acetate were used to carry out azide-acetylene reaction, and cellulose acetate was grafted with polyacrylonitrile to enhance the compatibility between the two, improve the interfacial interaction force, and avoid the phase separation phenomenon due to interfacial incompatibility between the two, so that the ultrafiltration membrane has higher tensile strength and elongation at break, and exhibits better mechanical properties.
[0061] Comparative Example 3 uses acetylene polyacrylonitrile copolymer and cellulose acetate as the substrate of the ultrafiltration membrane, and its tensile strength and elongation at break are lower than those of the embodiments. This is mainly because no grafting reaction occurs between the polyacrylonitrile copolymer and cellulose acetate, resulting in low compatibility and interfacial interaction between the two, and the added cellulose acetate has a low improvement in the mechanical properties of the ultrafiltration membrane.
[0062] Table 2 Ultrafiltration membrane filtration performance test
[0063]
[0064] After testing, compared with Comparative Examples 1 and 2, Examples 1-4 use acetyl cellulose grafted polyacrylonitrile obtained by the reaction of acetyl cellulose acetate copolymer and azido cellulose acetate as the substrate of the ultrafiltration membrane, and its water contact angle is significantly reduced, and the pure water flux increases greatly, mainly because the acetyl cellulose acetate copolymer contains hydrophilic carboxyl groups, and the acetyl cellulose reacts with azido cellulose acetate to generate triazole hydrophilic groups, so that the ultrafiltration membrane exhibits better hydrophilicity, which is beneficial to enhance the hydrophilicity and water flux of the ultrafiltration membrane. At the same time, the pollution index is reduced, the flux recovery rate is improved, and the anti-pollution performance of the ultrafiltration membrane to proteins is enhanced. This is because the ultrafiltration membrane has strong hydrophilicity and contains carboxyl and triazole groups, which have strong hydrogen bond interactions with water molecules, so that water molecules form a water film on the surface of the ultrafiltration membrane, reduce the contact between protein and the ultrafiltration membrane, and avoid protein attachment to the surface and pores of the ultrafiltration membrane, so that the ultrafiltration membrane exhibits better anti-pollution performance.
[0065] In Comparative Example 3, acetylene polyacrylonitrile copolymer and cellulose acetate are blended to prepare an ultrafiltration membrane, which does not contain triazole hydrophilic groups, resulting in the hydrophilicity, water flux and anti-pollution performance of the ultrafiltration membrane being lower than those in the examples.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A method for preparing a high-strength anti-pollution ultrafiltration membrane, characterized in that: The preparation method is: Step A, adding dimethyl sulfoxide, acrylonitrile, acrylate butyric acid amide alkynyl monomer into a reaction container, introducing nitrogen, adding azobisisobutyronitrile, stirring to react, cooling, pouring the solution into water for precipitation, filtering, washing, and drying to obtain an alkynyl polyacrylonitrile copolymer; The structural formula of the acrylate butyric acid amide acetylenic monomer is: ; Step B, add pyridine and cellulose acetate to a reaction container, heat to 55-60° C., stir, add 4-azidobenzoyl chloride, heat to 70-85° C., stir and react for 3-6 hours, cool, pour the solution into water for precipitation, filter, wash and dry to obtain azido cellulose acetate; Step C, adding N,N-dimethylformamide, acetylene polyacrylonitrile copolymer, and azido cellulose acetate into a reaction container, stirring and mixing, adding sodium ascorbate, copper sulfate, and water, passing nitrogen, stirring and reacting, cooling, pouring the solution into water for precipitation, filtering, washing, and drying to obtain cellulose acetate grafted polyacrylonitrile; Step D: add dimethyl sulfoxide and cellulose acetate grafted polyacrylonitrile into a container, stir to dissolve, and then stand to degas. Then pour the solution on the surface of a clean glass plate and cast and scrape the film. Then, soak the glass plate in distilled water to perform phase transformation to form a membrane. The obtained membrane material is immersed in distilled water for washing and drying to obtain a high-strength anti-pollution ultrafiltration membrane.
2. The method for preparing a high-strength anti-pollution ultrafiltration membrane according to claim 1, characterized in that: In the step A, the amount of acrylonitrile used is 100 parts by weight, the amount of acrylate butyric acid amide acetylenic monomer is 4-25 parts by weight, and the amount of azobisisobutyronitrile is 0.82-0.96 parts by weight.
3. The method for preparing a high-strength anti-pollution ultrafiltration membrane according to claim 1, characterized in that: In the step A, the reaction is carried out at a temperature of 60-70° C. for 5-8 hours.
4. The method for preparing a high-strength anti-pollution ultrafiltration membrane according to claim 1, characterized in that: In the step B, the amount of pyridine used is 1500-2000 parts by weight, the amount of cellulose acetate is 100 parts by weight, and the amount of 4-azidobenzoyl chloride is 5-40 parts by weight.
5. The method for preparing a high-strength anti-pollution ultrafiltration membrane according to claim 1, characterized in that: In the step C, the amount of alkynyl polyacrylonitrile copolymer is 100 parts by weight, the amount of azidoacetyl cellulose is 20-40 parts by weight, the amount of sodium ascorbate is 1.2-2.5 parts by weight, and the amount of copper sulfate is 0.7-1.6 parts by weight.
6. The method for preparing a high-strength anti-pollution ultrafiltration membrane according to claim 1, characterized in that: In the step C, the reaction is carried out at a temperature of 45-70° C. for 18-36 hours.
7. The method for preparing a high-strength anti-pollution ultrafiltration membrane according to claim 2, characterized in that: The preparation method of the acrylate butyric acid amide alkynyl monomer comprises: adding a solvent, propargylamine, and 2-bromoethyl acrylate into a reaction container to carry out a substitution reaction, then adding succinic anhydride to carry out an amidation reaction, concentrating the solution under reduced pressure, washing with methanol, and recrystallizing the product in dichloromethane to obtain the acrylate butyric acid amide alkynyl monomer.
8. The method for preparing a high-strength anti-pollution ultrafiltration membrane according to claim 7, characterized in that: The solvent is acetonitrile, tetrahydrofuran or 1,4-dioxane.
9. The method for preparing a high-strength anti-pollution ultrafiltration membrane according to claim 7, characterized in that: The usage of the propargylamine is 100 parts by weight, the usage of 2-bromoethyl acrylate is 320-360 parts by weight, and the usage of succinic anhydride is 190-220 parts by weight.
10. The method for preparing a high-strength anti-pollution ultrafiltration membrane according to claim 7, characterized in that: The substitution reaction is carried out at 30-40°C for 12-18 hours; the amidation reaction is carried out at 35-50°C for 2-5 hours.
Citation Information
Patent Citations
Polyacrylonitrile / nano-whisker composite ultrafiltration membrane and preparation method thereof
CN113457475A
Glycosyl modified acrylonitrile group nano fibre and its preparing method and application
CN101215736A
Preparation method of anti-pollution hydrophilic polysulfone membrane modified by amphiphilic amino acid
CN103877873A